Patient Experiences of Community Pharmacy Medication Supply and Medicines Reconciliation at Hospital Discharge: A Pilot Qualitative Study - Rhona Mundell; Derek Jamieson; Gwen Shaw; Anne Thomson; Paul Forsyth (MDPI AG, 2024)
(1) Background: As part of the Scottish Government's five-year recovery plan to address the backlog in NHS care following the COVID-19 pandemic, community pharmacies in Scotland are planned to provide a Hospital Discharge Medicines Supply and Medicines Reconciliation Service. We aimed to qualitatively explore patients' experiences with this new service. (2) Method: Adult patients (≥18 years age) who consented to participate in the Community Pharmacy Hospital Discharge and Medicines Reconciliation Service were invited for an interview within 21 days of discharge from hospital. Qualitative, one-to-one, semi-structured patient interviews were conducted by telephone and audio-recorded using Microsoft Teams®. The interview audio recordings were transcribed verbatim and underwent thematic analysis. (3) Results: Twelve patients were interviewed, evenly split by sex and with a median age of 62 years (range 36 to 88 years). Our analysis generated main five themes: patient engagement, stakeholder communication, practical factors, human factors, and comparative experiences. Many of these were interdependent. (4) Conclusions: Patients appreciated that the service ensured a quicker discharge from hospital. Good stakeholder communication, practical factors (including choice, location, and the realities of obtaining their medication from the community pharmacy), and a pre-existing and trusted relationship in their usual community pharmacy were the key factors that regulated the patient experience. Generally, patients were positive about the introduction of this new service. However, the lack of a previous relationship or trust with a community pharmacy, and previous experiences with medication supply problems were factors which had the potential to negatively impact patient experiences.